PENGUASAAN HURUF JEPANG DALAM MEMBACA TULISAN HIRAGANA PADA KELAS X JURUSAN USAHA PERJALANAN WISATA (UPW) DI SMK NEGERI 5 DENPASAR - Gede Bagus Wira Diputra (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2022)
This study was conducted to measure the extent of the ability of Vocational High School (Arts and Tourism) students to read one of the Japanese letters, namely Hiragana. The ability to read Hiragana is important to master to improve the competencies that exist in students in order to be able to compete in this increasingly dynamic world of tourism. This research was conducted at SMK Negeri 5 Denpasar in class X majoring in Travel Business Tours Class of 2022/2023. In this study, data collection techniques were used through the provision of tests by analyzing scores, percentages, and grouping result data between low, medium, and high. By using this technique, students can find out their ability to read Hiragana's writings.